Coffee and Cocoa By-Products as Valuable Sources of Bioactive Compounds: The Influence of Ethanol on Extraction - Blanca Martínez-Inda; Nerea Jiménez-Moreno; Irene Esparza; Carmen Ancín-Azpilicueta (Antioxidants)
Cocoa and coffee are two of the world’s most important crops. Therefore, their by-products are generated in large quantities. This work proposes a simple method for the valorization of these residues by obtaining phenolic compounds and melanoidins by solid–liquid extraction using different hydroalcoholic solutions as extracting solvents (0, 25, 50, 75, 100% ethanol). Extracts of both by-products presented the highest antioxidant capacity and total phenolic and melanoidin content when using 50–75% ethanol in the solvent. Among all the extracts, those obtained from spent coffee grounds at 75% ethanol showed the highest concentrations of total phenolic compounds (13.5 ± 1.3 mmol gallic acid equivalents/g dry matter) and melanoidins (244.4 ± 20.1 mg/g dry matter). Moreover, the sun protection factor values of the coffee extracts obtained with 50 and 75% of ethanol as extraction solvent (7.8 ± 0.9 and 8.5 ± 0.7, respectively) showed their potential for use in the cosmetic sector. The most important phenolic compounds identified in the coffee by-products extracts were phenolic acids, and most of them were found in higher concentration in extracts obtained with lower percentages of ethanol (0–25%). Protocatechuic acid was the most abundant phenolic in cocoa extracts, with concentrations ranging from 18.49 ± 2.29 to 235.35 ± 5.55 µg/g dry matter, followed by 4-hydroxybenzoic acid, (-)-epicatechin and (+)-catechin. Esculetin was found in both coffee and cocoa extracts, which had not been reported to date in these residues. In summary, the use of 75% ethanol as an extraction solvent seems a good strategy to obtain extracts rich in phenolic compounds from food by-products rich in melanoidins, such as coffee and cocoa by-products. The high antioxidant potential of these extracts makes them of great interest for the cosmetic and nutraceutical industries.